Mechanistic Research for the Student or Educator (Part I of II) - Leak, Rehana K.; Schreiber, James B. (Frontiers in Pharmacology, 2022)
Many discoveries in the biological sciences have emerged from observational studies, but student researchers also need to learn how to design experiments that distinguish correlation from causation. For example, identifying the physiological mechanism of action of drugs with therapeutic potential requires the establishment of causal links. Only by specifically interfering with the purported mechanisms of action of a drug can the researcher determine how the drug causes its physiological effects. Typically, pharmacological or genetic approaches are employed to modify the expression and/or activity of the biological drug target or downstream pathways, to test if the salutary properties of the drug are thereby abolished. However, experimental techniques have caveats that tend to be underappreciated, particularly for the newer methods. In this two-part series, the caveats and strengths of mechanistic preclinical research are described, using the intuitive example of pharmaceutical drug testing in experimental models of human diseases. This series is not intended to tackle the perpetual clash between the frequentist approach to statistics and other schools of thought. Rather, Part I focuses on technical practicalities and common pitfalls of cellular and animal models designed for drug testing, and Part II describes in simple terms how to leverage a full-factorial three-way ANOVA, to test for causality in the link between drug-induced activation (or inhibition) of a biological target and therapeutic outcomes. Upon completion of this series, the student is expected to appreciate the strengths as well as limitations of mechanistic research and to avoid some of its pitfalls.